Seeds for Needs, comprehensive package to promote selection of local varieties adapted to local conditions from national genebanks through farmers' use, using crowdsourcing and citizen science approaches - CGIAR Research Program on Water, Land and Ecosystems (2020)
This approach has been widely tested and validated among communities in Ethiopia and Uganda.